Altering the architecture of tissue engineered hypertrophic cartilaginous grafts facilitates vascularisation and accelerates mineralisation. - BUCKLEY, CONOR; VINARDELL, TATIANA; KELLY, DANIEL (My University, 2014)
Cartilaginous tissues engineered using mesenchymal stem cells (MSCs) can be leveraged to generate bone in vivo by executing an endochondral program, leading to increased interest in the use of such hypertrophic grafts for the regeneration of osseous defects. During normal skeletogenesis, canals within the developing hypertrophic cartilage play a key role in facilitating endochondral ossification. Inspired by this developmental feature, the objective of this study was to promote endochondral ossification of an engineered cartilaginous construct through modification of scaffold architecture. Our hypothesis was that the introduction of channels into MSC-seeded hydrogels would firstly facilitate the in vitro development of scaled-up hypertrophic cartilaginous tissues, and secondly would accelerate vascularisation and mineralisation of the graft in vivo . MSCs were encapsulated into hydrogels containing either an array of micro-channels, or into non-channelled ‘solid’ controls, and maintained in culture conditions known to promote a hypertrophic cartilaginous phenotype. Solid constructs accumulated significantly more sGAG and collagen in vitro , while channelled constructs accumulated significantly more calcium. In vivo , the channels acted as conduits for vascularisation and accelerated mineralisation of the engineered graft. Cartilaginous tissue within the channels underwent endochondral ossification, producing lamellar bone surrounding a hematopoietic marrow component. This study highlights the potential of utilising engineering methodologies, inspired by developmental skeletal processes, in order to enhance endochondral bone regeneration strategies.
PUBLISHED
Keywords: Cartilaginous tissue; Cartilaginous tissue; Next Generation Medical Devices